2009
DOI: 10.1111/j.1464-410x.2009.08600.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of repeated intradetrusor botulinum neurotoxin A injections on detrusor function in patients with neurogenic bladder dysfunction

Abstract: OBJECTIVE To evaluate the influence of repeated botulinum neurotoxin A (BoNT‐A) treatments on detrusor function in patients with neurogenic detrusor overactivity (DOA) due to spinal cord lesions. PATIENTS AND METHODS In a retrospective study, urodynamic evaluations of 27 consecutive patients with neurogenic DOA due to spinal cord lesions who received at least five BoNT‐A treatments were analysed. RESULTS After the first BoNT‐A treatment, bladder capacity, reflex volume, continence status and detrusor complianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 31 publications
1
39
0
2
Order By: Relevance
“…BoNT is a promising treatment for lower urinary tract dysfunction with profound basic and clinical implications [30] . Pannek et al [31] demonstrated the long-term efficacy of BoNT-A in neurogenic detrusor overactivity. On the contrary, Schulte-Baukloh et al raised the important subject of BoNT-A antibodies and therapy failure after long-term use of BoNT-A [32] .…”
Section: Reviewmentioning
confidence: 99%
“…BoNT is a promising treatment for lower urinary tract dysfunction with profound basic and clinical implications [30] . Pannek et al [31] demonstrated the long-term efficacy of BoNT-A in neurogenic detrusor overactivity. On the contrary, Schulte-Baukloh et al raised the important subject of BoNT-A antibodies and therapy failure after long-term use of BoNT-A [32] .…”
Section: Reviewmentioning
confidence: 99%
“…Nach der ersten Injektionstherapie zeigte sich eine Kontinenzrate von 93%, welche im Studienverlauf auf 74% nach der jeweils letzten Injektion abfiel [18].…”
Section: Risikofaktorenunclassified
“…Pannek et al [44] treated 27 patients with SCI with at least 5 (mean, 7.1) successive BTX-A injections. Continued efficacy was observed over time, with 74% considered to be treatment successes (based on urodynamic compliance and storage pressures as well as continence status).…”
Section: Botulinum Toxinmentioning
confidence: 99%